The effects of high level ascorbic acid on pregnancy rate and litter size in rats - Aydin, Muhterem; Yuksel, Murat (Academic Journals, 2011)
The effects of high dose ascorbic acid on pregnancy rate and litter size in rats were investigated in this study. For this purpose, forty rats were used. The animals were randomly divided into four groups as control (n = 10) and treatment (n = 30). The rats were randomly assigned to three groups in treatment group. Within this group, 15 females and 15 males were used. Females in Groups 1 and 3, and males in Groups 1 and 2 were administered 1.5 g/kg body weight vitamin C high dose ascorbic acid orally, in drinking water, freshly prepared daily for 15 days. The results showed that the use of high dose ascorbic acid in male Groups (1 and 2) caused an insignificant increment on pregnancy rate and litter size when compared to the control groups and Group 3. Thus, the use of high dose ascorbic acid may reduce fertilizing capability of sperm. On account of this, pregnancy rate may be falling away.
Keywords: Rat; ascorbic acid; pregnancy rate; litter size